Jamaica : Second Review Under the Stand-By Arrangement-Staff Report; Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
Economic activity is weak, but showing incipient signs of a recovery. Domestic financial markets remain stable and the growth outlook has improved. Better prospects for agriculture, mining and quarrying, and construction are expected to increase growth. Macroeconomic performance under the program continues to be positive. Jamaica has taken advantage of the favorable market conditions to ease monetary conditions and build international reserves, and continues to demonstrate a strong commitment to the program. The financial sector has weathered well the impact of the debt exchange.